Giotto: a toolbox for integrative analysis and visualization of spatial expression data - Dries, Ruben; Zhu, Qian; Dong, Rui; Eng, Chee-Huat Linus; Li, Huipeng; Liu, Kan; Fu, Yuntian; Zhao, Tianxiao; Sarkar, Arpan; Bao, Feng; George, Rani E.; Pierson, Nico; et al. (Genome Biology, 2021)
Spatial transcriptomic and proteomic technologies have provided new opportunities to investigate cells in their native microenvironment. Here we present Giotto, a comprehensive and open-source toolbox for spatial data analysis and visualization. The analysis module provides end-to-end analysis by implementing a wide range of algorithms for characterizing tissue composition, spatial expression patterns, and cellular interactions. Furthermore, single-cell RNAseq data can be integrated for spatial cell-type enrichment analysis. The visualization module allows users to interactively visualize analysis outputs and imaging features. To demonstrate its general applicability, we apply Giotto to a wide range of datasets encompassing diverse technologies and platforms.